تقدير محتوى الرصاص في غبار وأتربة جوانب الشوارع في مدينتي اللاذقية وحمص - الحكيم قصي (Latakia University Journal -Biological Sciences Series, 2019)
حددت تراكيز الرصاص في الغبار والأتربة المتراكمة على جوانب بعض الطرق الإسفلتية في مدينتي اللاذقية وحمص. جمعت العينات في ظروف جوية مستقرة وملائمة خلال مرحلة تحول القطر من استعمال البنزين المعالج بالرصاص إلى البنزين غير المعالج بالرصاص Unleaded عام 2006 , وقد حللت العينات باستعمال مطيافية الامتصاص الذري ( AAS ). بينت النتائج أن أعلى تركيز للرصاص خلال المرحلة الانتقالية في اللاذقية وجد في مواقع حي الصليبة القديمة وفي السوق المجاور لمحطة انطلاق الحافلات القديمة وفي سوق الخضر قرب ساحة أوغاريت, إذ بلغت التراكيز القصوى 47 , 39.1 ,38.2 ppm على التوالي. أما في مدينة حمص فكان أعلى تركيز للرصاص في عينات مواقع حي الحميدية وفي حي الخالدية إذ بلغت التراكيز القصوى 37.3 , 33.2 ppm على التوالي. وقد تمت مقارنة هذه التراكيز بأخرى للغبار والأتربة في بقاع أخرى من العالم، تظهر هذه الدراسة أنّ تراكيز الرصاص في العينات المدروسة هي ضمن التراكيز المسموح بها. بينت الدراسة أن استقرار الغلاف الجوي له تأثير كبير على توزع الرصاص إذ أن تركيز الرصاص ونمط توزعه قد تأثرا كثيرا باتجاه الرياح السائدة مما يؤدى إلى تفاوت في تراكيز الرصاص, و هذا التفاوت بين مناطق المدينة المختلفة وأحيائها هو مألوف ويتأثر بعوامل مختلفة مثل التخطيط العمراني. Lead levels were determined in dust and soils accumulated on the asphalt roadsides, in the cities of Lattakia and Homs. Samples were collected in stable and favorable weather conditions over the period of transition from the use of leaded to unleaded gasoline in 2006. Atomic absorption spectrometry (AAS) was used for Lead determination.The results showed that the highest concentration of lead during the transitional period in Latakia was found in three sites. the old neighborhood of Alsalibe,in the market next to the old bus station, and the old vegetable market near the square of Ugarit, with maximum levels of, 47, 39.1,and 38.2 ppm. respectively. In the city of Homs, the highest concentration of lead was found in two districts, Hamidiya and Khalidiya with maximum levels of 37.36,and 33.26 ppm respectively. These levels were compared with some other parts of world. The study showed that the levels of lead found in samples are in the permissible levels. The study showed that the stability of the atmosphere had a significant impact on the distribution of lead so that the concentration of lead and the pattern of distribution were affected by the direction of prevailing winds resulting in variation in lead levels. The disparity between different areas of the city and its neighborhoods is familiar and common and is affected by various factors such urban planning.